2020
DOI: 10.1177/0891988720944250
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Sleep Disturbances for Informal Carers of Individuals With PD and Dyadic Relationship: A Rural Perspective

Abstract: This study examines factors related to sleep disturbances, and the dyadic sleep relationship, in a convenience sample of 29 persons with Parkinson disease (PD) and spouse carer dyads living in regional Queensland. Carers completed questionnaires on sleep, depression, anxiety, carer burden, and well-being. Regarding carers, 66% reported sleep disturbances related to nocturnally care demands. Less than half of informal carers with a disturbed sleep had informed a health professional of this problem. Medication w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Caregivers also reported that they experienced sleep disruption due to care recipients’ night-time sleep symptoms such as hallucinations, delusions, agitation and unsettled behaviours 37. These findings are consistent with a study that reported 93% of caregivers report sleep disturbance, with the most common reason for disturbance being the care recipient Parkinson’s symptoms 47. In addition, another study found a statistically significant difference in caregiver sleep disturbances between caregivers who had sufficient health/social access and those who did not 29…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…Caregivers also reported that they experienced sleep disruption due to care recipients’ night-time sleep symptoms such as hallucinations, delusions, agitation and unsettled behaviours 37. These findings are consistent with a study that reported 93% of caregivers report sleep disturbance, with the most common reason for disturbance being the care recipient Parkinson’s symptoms 47. In addition, another study found a statistically significant difference in caregiver sleep disturbances between caregivers who had sufficient health/social access and those who did not 29…”
Section: Resultssupporting
confidence: 85%
“… 30 38 44 45 In addition, two of these studies found that caregiver sleep quality was also associated with care recipient depression scores. 30 44 When considering caregiver burden, greater levels of burden and caregiver distress are associated with decreased self-report sleep duration, 36 increased sleep disturbance 47 and sleep problems. 45 This may also be true for sleep quality, in which increased caregiver burden and higher severity of motor symptoms in Parkinson’s care recipient was associated with an increased odds of poor sleep.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations